2019
DOI: 10.1111/dth.13146
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial outcomes of tranexamic acid combination serum as a depigmenting agent for the use in healthy individuals

Abstract: To compare the effectiveness of tranexamic acid (TA) combination serum with hydroquinone, the gold standard in whitening agents for healthy populations. This was a three‐arm randomized controlled trial. The subjects were divided into three groups: the first group received 3% TA combination serum (3% TA, 4% galactomyces ferment filtrate, 2% niacinamide, and 4% alpha arbutin), the second group received 2% TA combination serum, and the third group received 4% hydroquinone. One milliliter of each serum was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Alternatively, it is possible to increase effectiveness by increasing the time of application and duration of the course of treatment. 1,9,20,24 Studies indicate that beneficial therapeutic effects can be obtained from TA preparations by administration once or twice daily, with the mean time of application being 8 to 12 weeks. 3,7,9,14,22, [25][26][27] In addition to its whitening effect, TA also reduces redness by influencing the superficial blood vessels in the area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is possible to increase effectiveness by increasing the time of application and duration of the course of treatment. 1,9,20,24 Studies indicate that beneficial therapeutic effects can be obtained from TA preparations by administration once or twice daily, with the mean time of application being 8 to 12 weeks. 3,7,9,14,22, [25][26][27] In addition to its whitening effect, TA also reduces redness by influencing the superficial blood vessels in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The most preferred concentration is in the range of 2% to 5% as preparations containing only tranexamic acid at low concentrations ≤5% offer effective decreases of hyperpigmentation; higher concentrations of 5% to ‐10% may cause irritation and do not demonstrate an increased effect. Alternatively, it is possible to increase effectiveness by increasing the time of application and duration of the course of treatment 1,9,20,24 . Studies indicate that beneficial therapeutic effects can be obtained from TA preparations by administration once or twice daily, with the mean time of application being 8 to 12 weeks 3,7,9,14,22,25‐27 …”
Section: Introductionmentioning
confidence: 99%
“…We found that the decreased melanogenesis caused by TA‐treated keratinocyte‐conditioned medium was partially (not fully) inhibited in the case of TGF‐β1 siRNA keratinocytes, which means TGF‐β1 plays a role in the regulation system. In addition, dermatologists have observed an overall improvement in the skin condition in TA‐treated melasma patients, including overall skin brightness, 27 relieved erythema 28 and reduced vessel numbers 29 in the dermis. Moreover, recent studies revealed that TA could prevent collagen degradation 30 and skin photoageing 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Many in vitro studies can be found in the literature showing arbutin's inhibitory effects on melanin synthesis [24-26]; however, the efficacy observed could hardly reach that of HQ. Several clinical studies have been performed in which arbutin was combined with other agents in formulations, e.g., niacinamide, bisabolol, retinyl aldehyde [27], or with tranexamic acid [28], showing to be as effective as 4% HQ in reducing pigmentation. According to some authors, arbutin is thought to work following its decomposition to HQ.…”
Section: Arbutinmentioning
confidence: 99%